Urban-industrial seascapes can be abundant and dynamic fish habitat - Bradley, Michael; Sheaves, Marcus; Waltham, Nathan J. (Frontiers in Marine Science, 2023)
Urban-industrial seascapes are prevalent around the world, yet we lack a basic understanding of how the mosaic of different habitats in these areas are used by mobile marine fauna, including features such as industrial ports and marinas. Urbanised areas have been alternately characterised in scientific literature as degraded, depauperate, or in some cases diverse and abundant. To advance our spatial and temporal understanding of the community of mobile marine fauna in these areas, we used repeated sonar image sampling over large swathes of two urban-industrial seascapes, combined with underwater video. 2,341 sonar segments were captured across Mackay Harbour and the Pioneer River estuary (North Queensland, Australia). We used this information to generate a preliminary understanding of the ecology of these locations. We found that overall, urban-industrial seascapes can contain counts of mobile marine fauna similar to natural areas, and that these seascapes are characterised by dynamic diel shifts in the spatial arrangement of mobile marine fauna in the water column. At night, large fish are prevalent in the water column, while during the day, assemblages are dominated by small fish. Within these urban-industrial seascapes, deeper areas containing heavy infrastructure such as ports can harbour large densities of fish, including heavily targeted fisheries species. These areas deserve recognition as marine habitat, are of consequence to fisheries, and have the potential to influence surrounding ecosystems. Important research questions remain regarding their impact on food webs and animal movement at larger scales.